Customer engagement and eWOM in tourism. Issue 3 (17th March 2020) - Kanje, Patrokil; Charles, Goodluck; Tumsifu, Elly; Mossberg, Lena; Andersson, Tommy
Abstract : Purpose: The purpose of this article is to examine the role of customer engagement (CE) on electronic word of mouth (eWOM) behavior among vacationers in Tanzania. The article disaggregates CE into cognitive process, affection and behavior and integrates eWOM passing into the eWOM concept. Design/methodology/approach: A sample of 278 vacationers who had used social media before and/or during their trip in Tanzania was used. They were drawn at three major airports in Tanzania when exiting the destination. Structural equation modeling (SEM) was used to test the proposed relationships. Findings: It is revealed that both the affective CE and behavioral CE positively relate to vacationers' eWOM seeking, giving and passing behaviors in tourism-related sites. On the other hand the cognitive CE relates positively only with eWOM passing behaviors. Research limitations/implications: The varied relationship of the three CE dimensions (cognitive, affective and behavioral) with eWOM behaviors further confirms the multi-dimensionality of CE and the enduring psychological connection of individuals beyond participation in activities. Practical implications: CE is multifaceted and enduring and thus managers should take a long-term, enduring and multidimensional perspective in facilitating CE development. Different content appeals are needed in facilitating CE in online platforms as CE dimensions relate variedly with eWOM behaviors Originality/value: The study links CE and eWOM in a novel way by disaggregating CE and integrating the eWOM passing component into the eWOM concept in tourism-related social media sites.